Simvastatin: between clinics and health economics - Costa, Francesco Vittorio; Zaniolo, Orietta (Farmeconomia. Health economics and therapeutic pathways, 2007)
Statins reduce the incidence of cardiovascular events, one of the most important public health problems and among the main leading causes of death. Their use has been increasing in the last decade and today they represent the first drug class in terms of public expenditure. In view of the introduction of generic simvastatin in the Italian market, this paper outlines a pharmacological and economic profile of this compound. Despite two decades of life, simvastatin remains competitive with other HMG-CoA inhibitors, inducing a dose-dependent, up to 43% cLDL reduction. In clinical trials evaluating hard endpoints, simvastatin treatment achieved a strong reduction of cardiovascular events, revascularization procedures and mortality. Review of the main published pharmacoeconomic studies on simvastatin consistently indicated good cost/effectiveness ratios in most geographic contexts; convenience of this therapy increases along with baseline cardiovascular risk. Among available statins inducing equivalent cholesterol reductions, generic simvastatin has the lowest daily costs. Assuming stable market volume, an estimated cost saving for the Italian National Health Service of about 1 million Euro per year is expected from the introduction of the generic drug. Further cost savings may accrue for a potential switch from more expensive statins to simvastatin. Albeit individual responses to statins are unpredictable, the choice to start with lower cost molecules can limit initial drug investment and dampen the negative financial impact of treatment interruptions and switches.